Annexins and cardiovascular diseases: Beyond membrane trafficking and repair - Méndez-Barbero, Nerea; San Sebastian-Jaraba, Irene; Blázquez-Serra, Rafael; Martín-Ventura, Jose L.; Blanco-Colio, Luis M. (Frontiers in Cell and Developmental Biology, 2022)
Cardiovascular disease (CVD) remains the leading cause of mortality worldwide. The main cause underlying CVD is associated with the pathological remodeling of the vascular wall, involving several cell types, including endothelial cells, vascular smooth muscle cells, and leukocytes. Vascular remodeling is often related with the development of atherosclerotic plaques leading to narrowing of the arteries and reduced blood flow. Atherosclerosis is known to be triggered by high blood cholesterol levels, which in the presence of a dysfunctional endothelium, results in the retention of lipoproteins in the artery wall, leading to an immune-inflammatory response. Continued hypercholesterolemia and inflammation aggravate the progression of atherosclerotic plaque over time, which is often complicated by thrombus development, leading to the possibility of CV events such as myocardial infarction or stroke. Annexins are a family of proteins with high structural homology that bind phospholipids in a calcium-dependent manner. These proteins are involved in several biological functions, from cell structural organization to growth regulation and vesicle trafficking. In vitro gain- or loss-of-function experiments have demonstrated the implication of annexins with a wide variety of cellular processes independent of calcium signaling such as immune-inflammatory response, cell proliferation, migration, differentiation, apoptosis, and membrane repair. In the last years, the use of mice deficient for different annexins has provided insight into additional functions of these proteins in vivo, and their involvement in different pathologies. This review will focus in the role of annexins in CVD, highlighting the mechanisms involved and the potential therapeutic effects of these proteins.